2013
DOI: 10.1371/journal.pone.0059310
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities Associated with the Surfaces of Fresh Fruits and Vegetables

Abstract: Fresh fruits and vegetables can harbor large and diverse populations of bacteria. However, most of the work on produce-associated bacteria has focused on a relatively small number of pathogenic bacteria and, as a result, we know far less about the overall diversity and composition of those bacterial communities found on produce and how the structure of these communities varies across produce types. Moreover, we lack a comprehensive view of the potential effects of differing farming practices on the bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
304
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(347 citation statements)
references
References 43 publications
(63 reference statements)
36
304
4
3
Order By: Relevance
“…Although likely an underestimate of the total diversity in these samples (Experimental Procedures), ∼2,400 observed OTUs represent four-to fivefold fewer than that observed in bulk soil samples and comparable to the levels that are observed in specialized niches like the rhizosphere (18,19). The specificity of the bacterial genera observed is supported by previous studies of analyses of fruit surfaces (20) (especially the apple phyllosphere) (21) and also microbiome studies of other fruit-associated animals like Drosophila (22,23). Particular bacterial phylotypes were identified from quite disparate habitats (e.g., a snail, a rotting apple, and a rotting orange), which could indicate their close association with C. elegans animals, but further studies of more habitats and C. elegans populations are needed to test this link.…”
Section: Resultssupporting
confidence: 80%
“…Although likely an underestimate of the total diversity in these samples (Experimental Procedures), ∼2,400 observed OTUs represent four-to fivefold fewer than that observed in bulk soil samples and comparable to the levels that are observed in specialized niches like the rhizosphere (18,19). The specificity of the bacterial genera observed is supported by previous studies of analyses of fruit surfaces (20) (especially the apple phyllosphere) (21) and also microbiome studies of other fruit-associated animals like Drosophila (22,23). Particular bacterial phylotypes were identified from quite disparate habitats (e.g., a snail, a rotting apple, and a rotting orange), which could indicate their close association with C. elegans animals, but further studies of more habitats and C. elegans populations are needed to test this link.…”
Section: Resultssupporting
confidence: 80%
“…Regarding fresh vegetables, they can harbor large and diverse populations of bacteria. A previous study [20] demonstrated significant differences in bacterial community structure dependent upon the type of vegetables involved, and also treatments undertaken in the course of production. In this context, several factors could play a role in the lower recovery of strains from raw food samples.…”
Section: Resultsmentioning
confidence: 94%
“…As a result, very little is known about the overall diversity and composition of microbial communities on harvested produce and how these communities vary across produce types. Based on recent studies on this topic (Rudi et al, 2002;Ponce et al, 2008;Ottesen et al, 2009;Rastogi et al, 2012;Leff and Fierer, 2013;), a few key patterns are emerging: (1) different produce types and cultivars can harbor different levels (abundances) of specific microbial groups (Critzer and Doyle, 2010), (2) farming and storage conditions can influence the composition and abundances of microbial communities found on produce, and (3) non-pathogenic microbes can interact with and inhibit microbial pathogens found on produce surfaces (Shi et al, 2009;Critzer and Doyle, 2010;Teplitski et al, 2011). Despite this recent body of work, we still have a limited understanding of the diversity of produce-associated microbial communities, their function, the factors that influence the composition of these communities after harvest and during storage, and the distribution of individual taxa (particularly those taxa that are difficult to culture) across different commodities.…”
Section: The Role Of the Microbiome In Fruit Health And Disease à A Nmentioning
confidence: 99%